Impact of Multidimensional Social Ties on Economic Well-Being Among MSMEs: The Moderating Role of Social Environment in the Digital Era - Ahda Segati; Muhammad Irwan Padli Nasution; Muhammad Habibi Siregar (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic development, particularly in emerging economies such as Indonesia. However, many MSMEs struggle to achieve sustainable economic well-being amid rapid digital transformation. This study examines the impact of multidimensional social ties bonding, bridging, and linking on MSMEs’ economic well-being and investigates the moderating role of social environment in the digital era. A quantitative approach was employed using a cross-sectional survey of 312 MSME owners. Method: Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both measurement and structural models, including moderation effects. Economic well-being was conceptualized as a multidimensional construct comprising income stability, financial security, and subjective well-being, while social environment was operationalized through digitalization, locality, and community support. Results: The findings demonstrate that all dimensions of social ties significantly influence economic well-being, with bridging social ties exhibiting the strongest effect. Furthermore, the social environment significantly moderates these relationships, strengthening the impact of social ties under favorable digital and community conditions. Conclusion: This study contributes to the literature by advancing social capital theory through a multidimensional and context-dependent perspective. Practically, the findings provide strategic insights for policymakers and MSME stakeholders to enhance resilience by strengthening social networks and improving digital and institutional ecosystems.